Evaluasi dan Perbaikan Desain Antarmuka Pengguna pada Aplikasi FOMO menggunakan Metode Usability Testing dan Pendekatan User-Centered Design - Fitria Adinda Rahmawati; Buce Trias Hanggara; Intan Sartika Eris Maghfiroh (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
FOMO application is mobile-based application that operates as a discussion forum for completely anonymous professionals to interact and share information in professional world, such as information related to employee salaries, office life and so on. Based on data from the Google Play Store and experience of researchers interacting with application, it was found that problems felt by users included, no notifications, unattractive user interface, inconsistent buttons, and frequent force closes. With these problems, it is necessary to evaluate application and provide recommendations for improving the user interface design of FOMO application. Interface design improvements are carried out using a User-Centered Design approach, while evaluation will be carried out using usability testing method. Evaluation of initial design and solution design was carried out to five respondents by working on a scenario task to obtain level of effectiveness and efficiency, and level of user satisfaction obtained by distributing system usability scale questionnaire. Interface design improvements were made by designing a low-fidelity user interface in form of wireframes and high-fidelity in form of mock-ups. In the initial design evaluation, a score of 58% was obtained for the effectiveness aspect, 51.28% for the efficiency aspect, and 59 for the user satisfaction aspect and found 17 problems with the user interface design. The results of evaluation solution design obtained an increase of 42% in aspect of effectiveness, 46.72% in aspect of efficiency, and 23.5 in aspect of user satisfaction.